Sleep after burn injuries: A systematic review and meta-analysis. (October 2022) - Lerman, Sheera F.; Owens, Michael A.; Liu, Tony; Puthumana, Joseph; Hultman, C. Scott; Caffrey, Julie A.; Smith, Michael T.
Abstract: Burn injuries are a complex medical condition associated with negative physical and emotional consequences including disturbances in sleep. The goals of this systematic review were to examine the prevalence of sleep disturbances in adult burn survivors and evaluate the effects of intervention to improve sleep. Eight electronic databases were systematically searched and yielded 49 studies (13 interventional and 36 non-interventional). Results from the systematic review demonstrate that a variety of sleep disturbances are common in burn survivors, persisting years after the injury and are associated with pain, itch, emotional distress and reduction in quality of life. Sleep assessment was primarily based on subjective measures and the available data did not allow for assessing the prevalence of sleep disorders in burn survivors. Results of the meta-analysis of four studies demonstrated that a variety of interventions improved sleep quality. These findings provide further evidence that sleep is compromised in burn survivors and highlight the need for ongoing assessment using a combination of validated self-reports and objective measures of sleep. More research is needed to determine the most effective treatments for sleep disorders in burn survivors and if early intervention will serve to improve long term outcomes.